Fungicides and insecticides can alter the microbial community on the cuticle of honey bees - Reiß, Fabienne; Schuhmann, Antonia; Sohl, Leon; Thamm, Markus; Scheiner, Ricarda; Noll, Matthias (Frontiers in Microbiology, 2023)
Honey bees are crucial for our ecosystems as pollinators, but the intensive use of plant protection products (PPPs) in agriculture poses a risk for them. PPPs do not only affect target organisms but also affect non-targets, such as the honey bee Apis mellifera and their microbiome. This study is first of its kind aiming to characterize the effect of PPPs on the microbiome on the cuticle of honey bees. We chose PPPs which have frequently been detected in bee bread and studied their effects on the cuticular microbial community and function of the bees. The effect of the fungicide Difcor® (difenoconazole), the insecticide Steward® (indoxacarb), the combination of both (mix A) and the fungicide Cantus® Gold (boscalid and dimoxystrobin), the insecticide Mospilan® (acetamiprid) and the combination of both (mix B) were tested. Bacterial 16S rRNA gene and fungal transcribed spacer region gene-based amplicon sequencing and quantification of gene copy numbers were carried out after nucleic acid extraction from cuticle of honey bees. The treatment with Steward® significantly affected fungal community composition and function. The fungal gene copy numbers were lower on the cuticle of bees treated with Difcor®, Steward®, and PPP mix A in comparison to the controls. However, bacterial and fungal gene copy numbers were increased in bees treated with Cantus® Gold, Mospilan® or PPP mix B treatment compared to the controls. Bacterial cuticular community composition of bees treated with Cantus® Gold, Mospilan® and PPP mix B differed significantly from the control. In addition, Mospilan® on its own significantly changed the bacterial functional community composition. Cantus® Gold significantly affected fungal gene copy numbers, community and functional composition. Our results demonstrate that PPPs show adverse effects on the cuticular microbiome of honey bees and suggest that PPP mixtures can cause stronger effects on the cuticular community than a PPP alone. The cuticular community composition was more diverse after the PPP mix treatments. This may have far reaching consequences for the health of honey bees.